2020
DOI: 10.1186/s13613-020-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Dosing vitamin C in critically ill patients with special attention to renal replacement therapy: a narrative review

Abstract: Rationale/methods The primary aim of the present contribution is to find a literature-based agreement on dose adjustments of vitamin C in critically ill patients undergoing renal replacement therapy (RRT). Available data/study results Critical illness is frequently accompanied by severe vitamin C deficiency. High-dose supplementation beneficially affects clinical outcome in small cohorts of patients with sepsis, burn injury, and trauma. There are no specific data on clinical outcomes in patients receiving ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 42 publications
0
26
0
4
Order By: Relevance
“…On the other hand, continuous oxidative stress is a potent trigger of inflammatory signalling to amplify the release of cytokines like tumour necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6) via the activation of nuclear factor‐κB (NF‐κB) pathway in hepatocytes and Kupffer cells, thus forming a positive feedback loop to recruit more neutrophils and lymphocytes and augment the damage of liver. Recently, some studies have revealed that the agents with anti‐oxidative capacity could effectively suppress the systemic immune response and improve the outcome of patients with sepsis 8,9 . However, whether septic liver injury could be relieved by the scavenging of ROS with some specific anti‐oxidative agents and thus bring benefits to sepsis treatment remains far from understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, continuous oxidative stress is a potent trigger of inflammatory signalling to amplify the release of cytokines like tumour necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6) via the activation of nuclear factor‐κB (NF‐κB) pathway in hepatocytes and Kupffer cells, thus forming a positive feedback loop to recruit more neutrophils and lymphocytes and augment the damage of liver. Recently, some studies have revealed that the agents with anti‐oxidative capacity could effectively suppress the systemic immune response and improve the outcome of patients with sepsis 8,9 . However, whether septic liver injury could be relieved by the scavenging of ROS with some specific anti‐oxidative agents and thus bring benefits to sepsis treatment remains far from understood.…”
Section: Introductionmentioning
confidence: 99%
“…High triglycerides and low HDL cholesterol are well-established cardiovascular risk factors for progressive atherosclerosis. One described beneficial effect of vitamin C is by inhibiting lipid peroxidation in HDL, thus preserving its antioxidant activity [ 25 ], as oxidation of HDL impairs cholesterol efflux capacity and its cardioprotective effect [ 26 , 27 ]. Although differences in HDL-cholesterol between KTR according to increasing tertiles of vitamin C, with respective mean values of 1.0, 1.1, and 1.2 mmol/L, may seem numerically marginal at first sight, it should be noted that small differences in HDL cholesterol may already be associated with relatively large differences in incidence of atherosclerosis-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…During a median follow-up of 9.5 (6.3-10.2) years, 75 (13%) patients developed graft failure (34,26, and 15 events over increasing tertiles of plasma vitamin C, log rank test p < 0.001). Univariate Cox proportional-hazards regression analyses of the association between tertiles of plasma vitamin C concentration and graft failure showed that patients in the highest tertile of plasma vitamin C when compared to those in the lowest tertile had a lower risk of developing graft failure (Table 2, HR 0.37; 95% CI 0.20-0.68).…”
Section: Prospective Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Morán et al [ 1 ] for their very attentive reading of our review on vitamin C dosing during renal replacement therapy [ 2 ], thereby noticing that one of the cited references [ 3 ] had been retracted. We used this retracted reference to support the assertion that a vitamin C dose up to 6 g/day was not contraindicated in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency.…”
mentioning
confidence: 99%